Fifteen-minute consultation—the child with a developmental disability: is there an ocular or visual abnormality?. Issue 6 (30th June 2017) - Salt, Alison; Sargent, Jenefer
Abstract : Objective: To present a structured approach for an outpatient consultation for a child with developmental disability who may have an ocular or visual disorder. Method: Review of relevant literature and description of the approach to ocular and visual assessment which could be used by any paediatrician. Conclusion: A systematic approach to history, observation and examination of a child with a developmental disability will assist in identifying a possible visual problem. A structured referral letter will ensure that the child will receive the most appropriate assessment to clarify the problem and appropriate management in the eye clinic.